GIMICS AS A POLITICAL COMMUNICATION APPROACH - Dharmajaya, Muhamad Agung; Muksin, Nani Nurani; Kaukab, M. Elfan; Jusoh, Wan Noor Hazlina Wan (Universitas Islam Negeri Mataram, 2024)
The use of political communication through gimmicks to increase candidate popularity continues to emerge, although traditional methods are still partly relevant. However, gimmicks without substance are a challenge for candidates and democratization. This research aims to see the relevance of gimmicks as an alternative to political communication. The method used in this research is descriptive qualitative. The findings show that gimmicks can be used as a political communication approach. Strengthening the gimmick is important, especially when offering the candidate's ideas. Political communication through gimmicks is too focused on entertainment and does not fully address the need for reform ideas in resolving public issues.